EMOSI TOKOH UTAMA DALAM NOVEL SEGALA YANG DIISAP LANGIT KARYA PINTO ANUGRAH (KAJIAN DAVID KRECH) - Yeti, Yeti; Seli, Sesilia; Wartiningsih, Agus (Universitas Tanjungpura, 2023)
This study aims to describe the emotions of the main character in the novel Everything That Sucks the Sky by Pinto Anugrah. This research uses descriptive methods and qualitative forms of research. The approach used is a literary psychology approach using David Krech's Perspective theory. The data source is a document in the form of a novel. The novel used is the novel Everything That Sucks the Sky by Pinto Anugrah. The technique carried out is a documentary study technique. The tools used are stationery and laptops. The results of this study show that the emotional analysis of Bungo Rabiah includes basic emotions, namely happy, angry, afraid, and sad. Emotions associated with sensory stimuli are pain, disgust, and pleasure. Emotions related to self-assessment are success, pride, shame, and regret. Emotions associated with others include love and hate. RPP has been designed by utilizing the novel Everything That Sucks the Sky by Pinto Anugrah as learning material, specifically to achieve KD 3.9 and 4.9 grade XII of high school.